2014
DOI: 10.1155/2014/795851
|View full text |Cite
|
Sign up to set email alerts
|

Traversable Ground Surface Segmentation and Modeling for Real-Time Mobile Mapping

Abstract: Remote vehicle operator must quickly decide on the motion and path. Thus, rapid and intuitive feedback of the real environment is vital for effective control. This paper presents a real-time traversable ground surface segmentation and intuitive representation system for remote operation of mobile robot. Firstly, a terrain model using voxel-based flag map is proposed for incrementally registering large-scale point clouds in real time. Subsequently, a ground segmentation method with Gibbs-Markov random field (Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Several studies have been conducted on reconstruction in both indoor and outdoor environments [30][31][32][33][34][35][36]. In the indoor environment, Izadi et al [30] and Popescu and Lungu [31] employed a Microsoft Kinect sensor.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have been conducted on reconstruction in both indoor and outdoor environments [30][31][32][33][34][35][36]. In the indoor environment, Izadi et al [30] and Popescu and Lungu [31] employed a Microsoft Kinect sensor.…”
Section: Related Workmentioning
confidence: 99%
“…Khatamian and Arabnia [32] reviewed several 3D surface reconstruction methods from unoriented input point clouds and concluded that none of them are able to run in real-time. In [33][34][35][36], the authors used one 3D laser range scanner combined with cameras and an IMU-GPS sensor for the outdoor environment. Because the features of ground and non-ground data are different, they have to be segmented and reconstructed separately.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations